Exploring the student’s visual reasoning in solving triangle and quadrilateral problems viewed from gender point of view - Prasetyo, Muhammad Ponco; Masduki (AIP conference proceedings, 2023)
The purpose of this study is to analyze the visual reasoning abilities of junior high school students based on gender using triangles and quadrilaterals. Subjects consist of two students with the provision that one male student and one female student. The data Collection technique was by conducting the visual reasoning tests on 10th and 8th grade students, then the selected subjects are interviewed. The validation of the data uses triangulation method. The data analysis technique uses three steps namely data reduction, data presentation, and conclusion drawing. The results of the study showed that male students were able to identify the shortest line, determine the position of the shortest distance, and calculate the shortest distance correctly and correctly in the triangle material. The male student is also able to identify an agricultural land, determine the length and width of agricultural land, and determine the area of agricultural land appropriately is the quadrilateral material. However, female students can only calculate the shortest distance correctly on the triangle material. In the the quadrilateral material female students can determine the length and width of the agricultural land on the rectangular material correctly.